Research progress on the psychological burden and intervention measures in cancer patients - Wang, Han-Qi; Lin, Hao; Liu, Bing (Frontiers in Psychiatry, 2024)
In the past 40 years, the gradually increasing incidence and mortality rates of malignant tumors have severely impacted the quality of life of patients, bringing significant physical and psychological burdens and becoming an increasingly serious social issue. With the development of medical standards, new methods for cancer detection and treatment have been continuously proposed. Although it has been proven that cancer is related to increased psychological burden and suicidal behaviors in patients, current research on the psychological burden caused by cancer is insufficient. Clinicians often overlook the psychological health issues of patients while treating their physical diseases. Considering the high incidence of cancer, this review will outline the psychological burdens of cancer patients worldwide in recent years and its high-risk factors. Moreover, this review will summarize the common methods for evaluating psychological burdens, present current predictive models and treatment methods for the psychological burden of cancer patients, aiming to provide a research basis and future direction for the timely and accurate assessment of the psychological burden in cancer patients.